Remission in antineutrophil cytoplasmic antibody-associated systemic vasculitis. - Mukhtyar, C; Hellmich, B; Jayne, D; Flossmann, O; Luqmani, R (2006)
The definition of remission in patients with systemic vasculitis must be distinguished from the term "cure," which implies that patients are well and not requiring ongoing therapy. Remission should be defined using a standardised approach to measuring clinical disease activity, and the definition should be qualified by the duration of the remission and the type of maintenance therapy required to sustain remission. Remission is an important goal of management in the systemic vasculitides and is achievable in most patients. Maintenance of remission is a more difficult target, and evidence from studies of patients with antineutrophil cytoplasmic antibody (ANCA)-associated systemic vasculitis indicates that durable, lasting remission is unlikely to occur. Despite good disease control, damage or scarring from disease or its treatment is a common finding and is a separate outcome from remission. Future studies of vasculitis therapies should address the concept of rapid and sustained disease control, so that patients spend most of their time in a state of good health, with minimal damage.